Zmiany u podstaw, czyli nowelizacja zasad ogólnych postępowania administracyjnego - Citko, Adam Grzegorz (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Amendments to the Act of 14 June 1960 — Code of Administrative Procedure J.L. No. 30, item. 168, as amended did not spare the general principles of administrative procedure. At first sight, they may seem to be merely cosmetic, but in practice they can raise many questions and problems. This article is dedicated to an attempt at finding the answers to these questions and solutions to encountered problems. It discusses each of the general principles and changes. It also indicates the practical importance of the general principles and their possible use in the administrative procedure.
Keywords: administrative procedure; general principles; amendments of administrative procedure; general principle of objective truth; general principle of written form